Metabolic imprint induced by seed halo-priming promotes a differential physiological performance in two contrasting quinoa ecotypes - Cifuentes, Leonardo; González, Máximo; Pinto-Irish, Katherine; Álvarez, Rodrigo; Coba de la Peña, Teodoro; Ostria-Gallardo, Enrique; Franck, Nicolás; Fischer, Susana; Barros, Gabriel; Castro, Catalina; Ortiz, José; Sanhueza, Carolina; et al. (Frontiers in Plant Science, 2023)
“Memory imprint” refers to the process when prior exposure to stress prepares the plant for subsequent stress episodes. Seed priming is a strategy to change the performance of seedlings to cope with stress, however, mechanisms associated with the metabolic response are fragmentary. Salinity is one of the major abiotic stresses that affect crop production in arid and semiarid areas. Chenopodium quinoa Willd. (Amaranthaceae) is a promising crop to sustain food security and possesses a wide genetic diversity of salinity tolerance. The aim of this work was to investigate the effect of seed halo-priming (P) on metabolic memory during salinity (S) in two contrasting Quinoa ecotypes (E) origins: Socaire from Atacama Salar, and BO78 from Chilean Coastal/lowlands. We found that ecotypes showed differential ability to germinate under saline conditions and to recover photosynthesis after salt shock, highlighting their differences in salt tolerance. During the vegetative stage, ecotypes presented large differences in the level of metabolites and by the effect of salinity, while 10 metabolites were dependent on the interaction E x S. The effect of seed HP in germination was dependent on the interaction of factors E x S x P, showing a more positive impact on the sensitive ecotype. Additionally, seed HP, promotes changes in the metabolomic profile in plants, including a reduction in carbohydrates (starch) and organic acids (citric and succinic acid), and an increase in antioxidants (ascorbic acid and α-tocopherol) and related metabolites. These changes were linked to a further reduced level of oxidative markers (methionine sulfoxide and malondialdehyde), allowing improvements in the energy use in PSII (ΦPSII) under saline conditions in the salt-sensitive ecotype. In view of these results, we conclude that seed HP prompts a “metabolic imprint” related to ROS scavenger at the thylakoid level, improving further ΦPSII in the most sensitive ecotype.